Influence of Social Media Marketing and Brand Awareness on Purchasing Decisions on Custom Cake Brand Oentukmu: Study on Follower’s Instagram Account Oentukmu - Gardilla, Humaira Fathma; Murtiyanto, Rizky Kurniawan; Afandi, Yosi (PT. Riset Press International, 2025)
The food and beverage (F&B) business has constantly been growing due to the significant and continuous market potential. With so many cake shops or specialty outlets offering custom cakes or aesthetic cakes in Malang City, each company has begun to present innovations in new concepts or characteristics to meet the tastes of consumers who are increasingly open to the development of existing trends. In order to compete to become the top brand recommendation for custom cake products, Oentukmu needs to create an attractive marketing strategy by utilizing social media marketing to support its promotional activities in order to position the brand in the minds of consumers to encourage the consumer purchasing decision process. This study aims to analyze the effect of social media marketing and brand awareness on purchasing decisions on Oentukmu brand custom cake products. This research was explanatory research with a quantitative approach. The data collection technique used a questionnaire distributed to 100 respondents, namely followers of the Oentukmu Instagram account. Respondents were selected using a purposive sampling technique. The data analysis used a questionnaire test, descriptive analysis, classical assumption test, multiple regression analysis, coefficient of determination analysis and hypothesis testing. The results of this analysis show that social media marketing and brand awareness together had a positive effect on purchasing decisions for Oentukmu custom cake products. This was supported based on the results of hypothesis testing (F test), with the Fcount value being 200.065 >Ftable 3.09 and sig. Value of 0.000 < 0.05. From the results of this study, it is hoped that Oentukmu can increase consumer interest and trust in Instagram social media marketing content created and maintain brand awareness strategies so that it has the opportunity to become the top brand of custom cake products so as to increase consumer purchasing decisions.